(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Flat feet is a change in the shape of the paw, which is expressed by a decrease in its longitudinal and transverse arc. Transverse and longitudinal flat feet are distinguished, there is a possibility that both forms can be observed together.